FIELD PERSISTENCE OF S-METOLACHLOR AND PENDIMETHALIN IN MAIZE-BASED CROPPING SYSTEM AND IMPACT ON EARTHWORM ACTIVITIES IN OGBOMOSO, NIGERIA (2014)
Application of chemicals on weed has been an effective method of weed control. However, this is with problems of persistence and hazardous effects on non-target organisms like arthropods. Common herbicides used in maize fields in Ogbomoso include atrazine, primextra, Lasso/atrazine, diuron pendimethalin, and S-metolachlor. Information on S-metolachlor and Pendimethalin persistence under field situations is inadequate. Therefore, persistence of S-metolachlor and Pendimethalin in maize field and their effects on earthworms were investigated. Information on the use of herbicide was collected from 120 randomly selected respondents from three out of five local government areas in Ogbomoso. S-metolachlor (0.8, 1.2, 1.6 L/ha), Pendimethalin (1.0, 1.5, 2.0 L/ha), hoe weeded, Weedy Check (WC) and mancozeb (2 kg ai/ha) (as toxic standard) were applied to maize (Oba super variety) plots. Soil and worm cast were randomly sampled for physico-chemical analyses Before Planting (BP) and worm cast alone at 90 Days After Planting (DAP). Maize seedling survivals at 14 DAP, weed biomass at 56 DAP and Maize Grain Yields were assessed. Earthworm density and species were determined using formalin extraction method at planting and 30 DAP. Soil samples were taken for herbicide residue analyses using spectrophotometry to determine Disappearance Time for 50% (DT50) of the herbicides. Lethal Concentrations for 50% (LC50) mortality on two earthworm species were determined by Contact Filter Paper (CFP) and Soil Test (ST). Data were analysed using descriptive statistics and ANOVA at α0.05. Thirteen herbicides including S-metolachlor and pendimethalin were being used. Approximately 37.4% and 21.4% of farmers used S-metolachlor (0.066 L/ha) and Pendimethalin (0.6 L/ha) which are below Recommended Rates (RR) of 1.6 L/ha and 2.0 L/ha respectively. Organic carbon (16.4 and 6.7 g/kg), nitrogen (1.3 and 0.5 g/kg), Phosphorus (15.6 and 5.9 mg/kg), Silt (210 and 80 g/kg), Clay (150 and 130 g/kg), and sand (640 and 790 g/kg) were obtained from worm casts and soil respectively BP. Phosphorus was significantly higher in worm casts 90 DAP (20.6 mg/kg) than BP (15.6 mg/kg). Seedling survivals at 14 DAP ranged from 90-94.2%. Weed biomass under S-metolachlor at 1.2 L/ha (26.6±7.9 g), Pendimethalin at 2.0 L/ha (27.2±7.2 g) and hoe weeded (33.0±8.3 g) were lower than WC (56.4±13.5 g). Maize grain yield under S-metolachlor at 1.2 L/ha (2111.1 kg/ha) and Pendimethalin at 2.0 L/ha (2244.7 kg/ha) were significantly higher than WC (602.2 kg/ha). Densities of Lumbricus terrestris (0.6±0.3), Eisenia fetida (0.9±0.3), and Libyodrilus violaceus (0.9±0.2) BP were lower at 30 DAP (0.8±0.2, 2.3±0.5 UNIVERSITY OF IBADAN LIBRARY iii and 0.9±0.1 respectively). The DT50 were 53.4, 53.8 and 55.4 days for 0.8, 1.2, and 1.6 L/ha respectively under S-metolachlor and 48.3, 57.3 and 37.9 days for 1.0, 1.5 and 2.0 L/ha respectively under Pendimethalin. The LC50 under S-metolachlor in CFP and ST respectively were E. fetida (1.6, 1.5 L/ha) and L. violaceus (0.5, 1.4 L/ha) while under Pendimethalin were E. fetida (1.9, 1.8 L/ha) and L. violaceus (2.6, 1.8 L/ha), which were lower than RR. S-metolachlor and Pendimethalin were moderately persistent. Their recommended rates gave highest maize grain yield, but were toxic to the two test earthworms. Keywords: Herbicide Persistence, maize yield, worm casts Word count: 499